(untitled) (Agro Productividad, 2021)
Objective: To evaluate non-linear and linear mathematical models used to estimate milk production per lactation, at different frequencies of milk weighing from records of Holstein (Ho), Brown Swiss (BS) cows and their crosses with Zebu (Z). Design/Methodology/Approach: The models evaluated were: Wood, Wilmink and Linear Interpolation. Daily records of milk production from 471 lactations of 72 cows were used; 1,884 records were created with frequencies of weekly, biweekly and monthly milk production. The following were included in the statistical model: the genotype (Ho X Z and SP X Z), birth season (rainy and dry), and number of lactation (1 and 2) with double and triple interactions. The statistical analyses were performed with GLM from MINITAB v17. The means were compared with Tukey’s test. Results: No differences were found (P?0.05) between the models for the average milk production per lactation in kg, obtained from daily measurements or estimated from weekly, biweekly and monthly data, although for the factors of birth season, number of lactation, and genotype they showed differences (P ? 0.05) in milk production per lactation. Study Limitations/Implications: Daily records of milk production are necessary to obtain production per lactation; the models applied predict milk production in a similar way in different frequencies of weighing in Holstein, Brown Swiss cows and their crosses with Zebu. Findings/Conclusions: The models used allow predicting the milk production per cow in a similar way in different frequencies of weighing.